Developing reading comprehension - Clarke, Paula J. (Hoboken : Wiley-Blackwell, 2013)
'Presents cutting-edge, evidence-based interventions for dealing with specific difficulties of reading comprehension in children aged 7-11. An in-depth introduction to the'poor comprehender profile', which describes children who despite being fluent readers have difficulty extracting meaning from text. Sets out a range of practical interventions for improving reading skills in this group - along with comprehensive guidance on assessment and monitoring, and insightful accounts of professionals' experience in delivering the techniques described. Includes an overview of psychological theories of reading comprehension, evaluating their practical applicability.'--
'An in-depth introduction to the 2018 poor comprehender profile', which describes children who despite being fluent readers have difficulty extracting meaning from text'--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Reading comprehension; Reading comprehension -- Study and teaching (Elementary); EDUCATION -- Teaching Methods & Materials -- Reading & Phonics; Reading comprehension; Reading comprehension -- Study and teaching (Elementary); Electronic books